Exploring Protean Career Orientation: Career Strategies for Generation Z in the 21st Century - Alamsyah, Muh. Nur; Atmoko, Adi; Hidayah, Nur; Peng, Yang (Indonesian Journal of Learning Education and Counseling, 2025)
This study aims to explore protean career orientations in developing Generation Z's 21st century career adaptability in an educational context. Generation Z faces significant challenges in a dynamic and fast-changing learning environment, including technological developments, labor market changes, and evolving skill needs. Therefore, it is important to understand how a protean career orientation can help them adapt to these changes. The method used was Systematic Literature Review (SLR), which identified and analyzed the literature related to protean career orientation and career adaptability. The results showed that protean career orientation, which emphasizes flexibility, career self-management and the ability to learn lifelong, significantly contributes to the development of career adaptability. The findings highlight the importance of developing adaptive skills and mindsets to enable Generation Z to cope with the evolving demands of education and careers. Adopting a protean career orientation can be an effective strategy in preparing Generation Z for future career challenges and enhancing their ability to navigate diverse educational and career pathways so that they can reach their full potential in an ever-changing environment.